IDENTIFIKASI NUTRISI DAN SENSORI BIJI KAKAO (Theobroma cacao L.) DENGAN MEDIA FERMENTOR KOTAK KAYU DAN DAUN PISANG DALAM PENGOLAHAN COKELAT BUBUK - Bigi Undadraja (Jurnal WACANA PERTANIAN, 2020)
Cocoa beans are the product of the cocoa plant which is then dried to reduce moisture content, before being processed into food, beverage, pharmaceutical, and cosmetic products. To improve the quality of cocoa beans, fermentation is carried out before drying, fermentation of cocoa beans is carried out using wooden box fermenter media and banana stone leaves. The research objective was to determine the quality of cocoa beans produced from 2 fermenter media. This study used proximate analysis to determine the nutritional content and sensory tests of aroma, texture, color of cocoa powder by 20 panelists using the scoring method, then the data were discussed descriptively. The results showed that the fermented cacao beans using banana leaves had higher fiber nutrition 21.7727%, protein 10.7182%, and the fat and free fatty acid content was lower than that of wooden box fermentation, namely 24.9145% and 6.4315%. In the sensory test, cocoa beans fermented using banana leaves got the highest and preferred value from the panelists, namely aroma parameters 4.55%, texture 4.85%, and color 4.6%.